Topically Applied Connective Tissue Growth Factor/CCN2 Improves Diabetic Preclinical Cutaneous Wound Healing: Potential Role for CTGF in Human Diabetic Foot Ulcer Healing. (18th February 2015) - Henshaw, F. R.; Boughton, P.; Lo, L.; McLennan, S. V.; Twigg, S. M.
Abstract : Aims/Hypothesis . Topical application of CTGF/CCN2 to rodent diabetic and control wounds was examined. In parallel research, correlation of CTGF wound fluid levels with healing rate in human diabetic foot ulcers was undertaken. Methods . Full thickness cutaneous wounds in diabetic and nondiabetic control rats were treated topically with 1  μ g rhCTGF or vehicle alone, on 2 consecutive days. Wound healing rate was observed on day 14 and wound sites were examined for breaking strength and granulation tissue. In the human study across 32 subjects, serial CTGF regulation was analyzed longitudinally in postdebridement diabetic wound fluid. Results . CTGF treated diabetic wounds had an accelerated closure rate compared with vehicle treated diabetic wounds. Healed skin withstood more strain before breaking in CTGF treated rat wounds. Granulation tissue from CTGF treatment in diabetic wounds showed collagen IV accumulation compared with nondiabetic animals. Wound α -smooth muscle actin was increased in CTGF treated diabetic wounds compared with untreated diabetic wounds, as was macrophage infiltration. Endogenous wound fluid CTGF protein rate of increase in human diabetic foot ulcers correlated positively with foot ulcer healing rate (r = 0.406 ;P < 0.001 ). Conclusions/Interpretation . These data collectively increasingly substantiate a functional role for CTGF in human diabetic foot ulcers.